Stieleriacines, N-Acyl Dehydrotyrosines From the Marine Planctomycete Stieleria neptunia sp. nov. - Sandargo, Birthe; Jeske, Olga; Boedeker, Christian; Wiegand, Sandra; Wennrich, Jan-Peer; Kallscheuer, Nicolai; Jogler, Mareike; Rohde, Manfred; Jogler, Christian; Surup, Frank (Frontiers in Microbiology, 2020)
Bacteria of the phylum Planctomycetes occur ubiquitously in marine environments and play important roles in the marine nitrogen- and carbon cycle, for example as scavengers after phototrophic blooms. Here, we describe the isolation and characterization of the planctomycetal strain Enr13T isolated from a Posidonia sp. biofilm obtained from seawater sediment close to Panarea Island, Italy. Phylogenetic tree reconstruction based on 16S rRNA gene sequences and multi-locus sequence analysis supports the delineation of strain Enr13T from characterized species part of the phylum of Planctomycetes. HPLC-MS analysis of culture broth obtained from strain Enr13T revealed the presence of lipophilic metabolites, of which the major compound was isolated by preparative reversed-phase HPLC. The structure of this compound, named stieleriacine D (1), was elucidated utilizing HRESIMS, 1D- and 2D-NMR data as a new N-acylated dehydrotyrosine derivative. Its biosynthesis was proposed based on an in silico gene cluster analysis. Through analysis of the MS/MS spectrum of 1 and its minor derivative, stieleriacine E (2), it was possible to assign the structure of 2 without isolation. 1 showed antibacterial activity, however, the wide distribution of structurally related compounds indicates a potential role as a signaling molecule.